Substrate casing and compost supplementation in button mushroom cultivation - Pardo-Giménez, Arturo; Figueirêdo*, Vinícius Reis de; Zied, Diego Cunha; González, José Emílio Pardo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to describe the behavior of pine bark, coconut fiber, and spent mushroom substrate, as casing layers, in the button mushroom (Agaricus bisporus) cultivation. After the physical, chemical and biological characterization of these casing layers, qualitative and quantitative yield parameters were evaluated in a mushroom crop cycle with four crops. The lower porosity and water retention capacity of the mineral soil without additives and the high eletrical conductivity of the post culture substrate of the mushroom used, associated with nutrient supplementation, are the determinant factors of the different agronomical behavior observed. The casing mixtures influenced mushroom yield, number of mushrooms, biological efficiency, production rate, and earliness. The best total yield was obtained using mineral soil mixed with supplemented coconut fiber. The evaluated casing layers can be used commercially for button mushroom production.